1987
DOI: 10.1159/000174199
|View full text |Cite
|
Sign up to set email alerts
|

Compensated Cardiogenic Shock: A Subset with Damage Limited to Liver and Kidneys

Abstract: A variant of compensated cardiogenic shock occurring in patients with chronic congestive heart failure following an episode of pulmonary edema, and in the absence of hypotension, is described. The clinical picture is characterized by combined renal and hepatic injury and a severe, often fatal, course and is distinct from other subsets of cardiogenic shock. When the splanchnic vasodilator dopamine was added to the patients’ management, the outcome was uniformly favorable. This variant of compensated cardiogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Low-dose dopamine may impede the development of hypoxic liver injury [36]. However, dopamine was not used in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Low-dose dopamine may impede the development of hypoxic liver injury [36]. However, dopamine was not used in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…That being said, an ideal inotropic agent has not yet been identified, and the existing studies have reported only limited benefit in specific clinical circumstances. For example, dopamine may offer a survival benefit for patients with normotensive cardiogenic shock and kidney injury, 54 and dobutamine has been proposed to augment splanchnic blood flow to the liver in patients with low cardiac index. 55 The findings from these small studies are not widely generalizable, however.…”
Section: Managementmentioning
confidence: 99%
“…Naschitz et al reported improvement of outcome in patients with nonhypotensive cardiogenic shock accompanied by renal and hepatic injury after administration of dopamine [89][90][91]. Others observed in a small retrospective study that patients (n = 28) receiving calcium-channel blockers and/or antiarrhythmic drugs had a higher mortality risk [92] and suggested that this may be a consequence of decreased clearance of hepatic drugs and altered cardiac sensitivity.…”
Section: The Liver As a Therapeutic Targetmentioning
confidence: 99%